A training intervention to improve frontline construction leaders' safety leadership practices and overall jobsite safety climate. (September 2019) - Schwatka, Natalie V.; Goldenhar, Linda M.; Johnson, Stefanie K.; Beldon, Marissa A.; Tessler, Jamie; Dennerlein, Jack T.; Fullen, Mark; Trieu, Hao
Abstract: Introduction : The 2.5 h Foundations for Safety Leadership (FSL) training program teaches construction supervisors the leadership skills they need to strengthen jobsite safety climate and reduce adverse safety-related outcomes. Methods : Using a quasi-experimental prospective switching replications study design, we examined (1) if FSL-trained jobsite safety leaders would report improved understanding and practice of the FSL leadership skills, safety practices and crew reporting of safety related conditions, and (2) if their crew perceived a change in (a) their supervisors' practices, (b) their own safety practices and reporting of safety-related conditions, and (c) overall jobsite safety climate. Twenty construction sub-contracting companies were recruited and randomly assigned to either an early or lagged-control training group. Participating supervisors and workers completed surveys at multiple time points before and after the FSL training. We used linear mixed modeling to test changes over time. Results : Only supervisors in the early group reported a statistically significant improvement in their understanding and practice of the leadership skills as well as safety practices from before to 2- and 4-weeks post-training. Overall, no significant change was detected in crew-reported outcomes from before to after their supervisors' participated in the FSL training. Conclusions: These results provide evidence that the FSL training can, at least in the short-term, improve construction frontline leaders' jobsite leadership skills. Future research could include an evaluation of FSL refresher activities and a longer-term follow-up. Practical applications: The Foundations for Safety Leadership (FSL) program fills an identified need for construction frontline supervisors to learn and practice critical safety leadership skills on the jobsite. It has already reached over 60, 000 leaders and has the potential to reach over 100, 000 each year during either an OSHA 30-h or a stand-alone course. Highlights: This study evaluated the 2.5-h Foundations for Safety (FSL) training program for construction supervisors. FSL-trained supervisors reported an improvement in their understanding and practice of the leadership skills. We did not observe a significant change in crew-reported outcomes from before to after their supervisors participated in the FSL training.